The Role of Advocates and Paralegals in the Implementation of Providing Legal Aid and Assistance to the Community - Rochman, Auliya; Ratih, Ayuk Nila (Law Research Review Quarterly, 2021)
The principle of community and state life in a constitutional state certainly requires the participation of advocates as a free, independent, and responsible profession in terms of legal assistance in the context of criminal law enforcement, in addition to the role of judicial institutions and existing law enforcement agencies such as the police and judiciary. Legal aid is a legal service provided by legal aid providers to recipients of legal aid free of charge. Legal aid is a form of human rights to achieve access to justice, equality before the law, fair trial. With the provision of legal aid, it is hoped that it will be able to prevent the accused or suspect from arbitrary law enforcement is facing a legal case. Based on the legal services provided, in carrying out their duties and profession, advocates are carried out for the sake of upholding legal justice and the interests of the community in seeking justice, as well as upholding their fundamental rights in the eyes of the law. The law on legal aid now expands the definition of legal aid recipients so as to provide opportunities for PTN lecturers, paralegals, and law students who are members of LBH to carry out community service and also the development of legal knowledge.